Effect of Calcium of Lactose Free Millet Milk on Growth and Development in Albino Weanling Rats - Kimeera Ambati, Dr. K. V. Sucharitha, Prof. K. Thyagaraju (International Journal of Advanced Science and Technology, 2020)
Background:Calcium, the very important mineralhelps in growth and development ofinfants.Calcium helps in building strong bones, teeth,proper functioning of nerves and muscle, blood clot and in activating the enzymes that convert food into energy. Infants and Children are growing new bone all the time, they need continuous supply of calcium to support the healthy growth.Milk is the only food for infants which is richest source of calcium. Some infants are sensitive to lactose in milk because they have Lactose Intolerance. The present study aimsto develop an alternate milk forlactose intolerance infants with finger millet and pearl millet.Method:Traditional methods were used to process the milletswhich help in retaining and increasing the nutritional content in millets.The millet milk was analyzed for calcium content using the ICPMS.The millet milk was supplemented for 6 weeks to albino rats in comparison with cow milk. The tibia weight and length were measured and calcium content in tibia was analyzed. Result:The calcium content of the millet milk was 80mg/100mlwhere as in cow milk it was 120mg/100ml.The mean calcium content of the tibia inalbino rats was15.35±3.50mg/dl fed with millet milkand20.40±3.74mg/dl in rats fed with cow milk.Conclusion: The developed millet milk contain good amount of calcium on par with cow’s milk, it can be used as substitute milk for lactose intolerant infants.